Capacity Building at the Kurdistan Region Statistics Office Through Data Collection - Abramzon, Shmuel (RAND Corporation, 2014)
The Kurdistan Region of Iraq needs policy-relevant data to help improve infrastructure, encourage the private sector, attract foreign investment, and foster economic growth. The Kurdistan Region Statistics Office needs to build capacity to collect the data. RAND worked closely with the Office to build capacity by preparing, conducting, and analyzing the first round of a survey of the regional labor force.